2023
DOI: 10.3390/ijerph20031957
|View full text |Cite
|
Sign up to set email alerts
|

The Mediation of Care and Overprotection between Parent-Adolescent Conflicts and Adolescents’ Psychological Difficulties during the COVID-19 Pandemic: Which Role for Fathers?

Abstract: Background: There is evidence of a significant raise in youths’ emotional and behavioral difficulties during the pandemic. Only a few studies have addressed parent-adolescent conflict, and none investigated the possible mediating effect of parenting in the association between conflicts with parents and adolescents’ symptoms. This study aimed at investigating youths’ psychological symptoms during the pandemic, focusing on the predicting effect of parent-adolescent conflict. The mediating role of care and overpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 98 publications
2
3
0
Order By: Relevance
“…The correlation analyses' outcomes suggest that parental care is negatively associated with parental overprotection. This pattern of results agrees with the international literature (e.g., Forresi et al, 2023;Ge et al, 2023;Gong et al, 2022;Khalid et al, 2018;Lyons et al, 2017;Parker et al, 1979;Rikhye et al, 2008;Stearns & McKinney, 2020;Sultan et al, 2019;Tani et al, 2018;Xu et al, 2018) and with the current study's hypothesis. It is suggested that offspring's perception of parental care during childhood and adolescence is associated with increased resilience and the development of emotional regulation skills and that opposite results are displayed when regarding parental overprotection (Sameshima et al, 2020;Tani et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The correlation analyses' outcomes suggest that parental care is negatively associated with parental overprotection. This pattern of results agrees with the international literature (e.g., Forresi et al, 2023;Ge et al, 2023;Gong et al, 2022;Khalid et al, 2018;Lyons et al, 2017;Parker et al, 1979;Rikhye et al, 2008;Stearns & McKinney, 2020;Sultan et al, 2019;Tani et al, 2018;Xu et al, 2018) and with the current study's hypothesis. It is suggested that offspring's perception of parental care during childhood and adolescence is associated with increased resilience and the development of emotional regulation skills and that opposite results are displayed when regarding parental overprotection (Sameshima et al, 2020;Tani et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…It is suggested that mothers display more negative educational practices and anxiety when the child who exhibits behavioral problems is a girl than when it is a boy (Maia & Soares, 2018;Song et al, 2022). The combination of conflicts with parents experienced during adolescence and behavioral difficulties may negatively affect parenting, leading mothers and/or fathers to become more overprotective and express lower levels of care (Forresi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to provide a phenomenological explanation of parent-adolescent conflict among girls aged 14 to 17 years. The findings align indirectly with the prior research (Cao & Tam, 2023;Forresi et al, 2023;Goering & Mrug, 2023;Haverfield & Theiss, 2023;Javidi et al, 2015;Keshavarz et al, 2020;Khodaei et al, 2021;LoBraico et al, 2020;Marshall et al, 2023;Mastrotheodoros et al, 2020;Mokhtarnai et al, 2021;Mokhtarnia et al, 2016;Sadatian et al, 2020;Valinezhad et al, 2021;Yousefi et al, 2021). The results of this study revealed that the most significant factors contributing to parent-adolescent conflict included 7 main themes and 23 sub-themes.…”
Section: Discussionsupporting
confidence: 89%
“…Some adolescent girls attributed conflicts with their parents to the existing conflicts between the parents themselves, leading to a tense family atmosphere. Forresi et al (2023) noted that in families with parental conflicts, children also experience friction and damage, particularly adolescents, who reflect this conflict in their relationships with parents (Forresi et al, 2023). Another sub-theme, being an only child, was mentioned by participants as leading to increased parental attention and expectations, along with more intense supervision and control (Mokhtarnai et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of changes in work, life, and learning styles, parents and their children have experienced extraordinary pressure. Several studies have demonstrated that helicopter parenting in such extreme circumstances may have more adverse consequences on children's mental health and conduct, potentially impairing their ability to develop the psychological resilience needed to cope with adversity [70][71][72]. In the foregoing context, this study found that helicopter parenting leads to significant negative consequences for college students.…”
Section: Conclusion and Discussionmentioning
confidence: 60%